Palliative intubation for malignant strictures of the oesophagus - Leverment, J. N. (1974)
Leverment, J. N. and Mearns Milne, D. (1974).Thorax, 29, 228-231. Palliative intubation for malignant strictures of the oesophagus. Over a 16-year period the Mousseau-Barbin tube was used for palliation in 50 patients suffering from malignant stricture of the oesophagus. In only two cases was the Souttar tube used. Thirty-seven cases were intubated as a primary method of treatment—21 cases without preliminary exploration, 13 cases following exploration, and three cases as a `delayed' procedure. Twelve cases were secondarily intubated as a result of recurrence of malignancy following an earlier oesophagogastrectomy. In three cases perforation of the oesophagus was recognized at the time of intubation, following which palliative oesophagogastrectomies were attempted. Intubation remains one method of relieving the patient's most distressing symptom, but in the majority of cases prolongation of life was seldom for more than three months. The hazards of this form of treatment are discussed.